Factor structure of the brief COPE in spouses of women with gynecological cancer - Li, Ziye; Zhang, Wanluan; Zhou, Lihua; Wang, Weili (Indian journal of cancer, 2025)
Abstract Objective: The purpose of the current study was to verify the factor structure of the Brief Coping Orientation to Problems Experienced (Brief COPE) inventory among spouses of women with gynecological cancer. Design: A descriptive study was conducted involving 351 spouses of gynecological cancer patients admitted to a hospital. Setting: Gynecological ward of a tertiary hospital of China. Main Outcome Measure: Confirmatory factor analysis and exploratory factor analysis were performed to test the factor structure of Brief COPE among participants. Results: The results showed that the soundness of data fitting three previous models of spouse caregivers were poor. A new three-factor structure was identified: avoidant coping (12 items), active coping (8 items), and seeking support (4 items), with four original items dropped. Conclusion: The findings suggest that the new three-factor structure has good construct validity, which can be used to measure the coping strategies of spouses of women with gynecological cancer.